The Fiscal Framework and Urban Infrastructure Finance in China - Su, Ming; Zhao, Quanhou (World Bank, Washington, DC, 2012)
China has experienced more than 25 years of extraordinary economic growth. Underlying this growth has been a decentralized fiscal system, in which provinces and large cities are given the freedom to make infrastructure investments to stimulate local development, and are allowed to retain a large part of the fiscal revenues that are generated from economic activity. Although successful as a growth strategy, this policy created two problems for national fiscal management. First, it significantly reduced the central government's share of fiscal revenues, which fell from 34.8 percent in 1980 to 22 percent in 1992. Second, it widened economic and fiscal disparities between the rapidly growing urban coastal region and the rest of the country. Rapid growth in subnational debt (which rose 23-fold in a decade) and subnational nonperforming loans (estimated by the authors to range between US$100 billion and US$150 billion) has placed pressure on China's financial system. Traditionally, China has favored bank lending as a source of finance because the banking system has provided a vehicle for central political control over local debt. But as China's financial system matures, creditworthiness standards must become more important. The authors recommend greater use of the revenue streams from infrastructure assets as a financing source, and gradual relaxation of central political control over subnational debt. One step in this direction would permit leading cities to issue municipal bonds based on objective financial standards.